Supporting Sustainable Communities in Slum Settlement Areas by Optimizing Geospatial Technology and Land Management Approaches in Kertapati District, Palembang - Falensky, M.A.; Aqshal, J.; Sari, F. P. L.; Farabi, A. (GMPI Conference Series, 2023)
Slum areas have always been a concern in development planning. In fact, this has become one of the goals of the 2030 Sustainable Development Goals (SDGs), especially Sustainable Cities and Communities. According to the United Nations Development Program (UNDP), in the coming decades, 828 million people are estimated to live in urban slums and this number will continue to increase. While in Indonesia, there are slum areas covering an area of 86,548 hectares, 28% of which are located on the island of Sumatra. Palembang, one of the big cities in Sumatra, also faces the problem of slum settlements in its urban area, which is 3,607 hectares. This study aims to determine the level of slums in the residential area in Kertapati District which is included in the slum area in Palembang City and furthermore, recommends the concept of land management as a solution to these problems. The variables used in this study consisted of the physical variables of settlements, basic infrastructure and land ownership. Data on building density, building layout and building construction are used to describe the physical variables of settlements. While the basic infrastructure variables are explained by data on clean water infrastructure, solid waste infrastructure, drainage infrastructure, residential road infrastructure and sanitation infrastructure. For the variable of land ownership, data on status and land ownership are used. The data was obtained through Sentinel 2A satellite imagery in 2022 and from conducting field surveys and in-depth interviews with several local residents. Furthermore, the data was analyzed using a map overlay-based scoring of each variable using a Geographic Information Systems. The results of this study obtained a map of each variable level of settlement slums and a map of the slum level of settlements in Kertapati District with the level of settlement slums divided into light slum classes in 2 villages with a percentage of 11.51%, medium slum class in 1 village with a percentage of 35.96% and heavy slum class in 3 villages covering 52.53% of the total area of Kertapati District. This shows that the settlements in Kertapati District are dominated by heavy class slums, so this study recommends the concept of Land Consolidation land management with the Land Readjustment approach as an alternative to handling slum areas in Kertapati District, Palembang City.